Body mass index in mother and child dyads and its association with household size and parents’ education in 2 urban settings of Yucatan, Mexico - Paulina Cauich-Vinas; Hugo Azcorra; Luis Rodriguez; Sudip Datta Banik; Maria Ines Varela-Silva; Federico Dickinson (2019)
Background: Overweight/obesity (OW/OB) coexists in mother-child dyads. However, dearth of evidence on the factors associated with this phenomenon calls for research. Objective: To analyze the association of sociodemographic factors with OW/OB in a sample of 260 Maya mother-child dyads from Yucatan, Mexico. Methods: During 2011-2014 we measured height and weight in children and their mothers and calculated their body mass index (BMI). The OW/OB cut-off points were defined, for mothers, as having a BMI >25kg/m2 and, for children, as having a BMI-for-age >2SD of the World Health Organization references. Mother-child dyads were grouped according to their BMI status: 1) normal weight mother and child, 2) normal weight mother and OW/OB child, 3) OW/OB mother and normal weight child, and 4) OW/OB mother and child. A multinomial logistic regression model was used to analyze the interrelationships among BMI status in mother-child dyads, household size and parental education. Results: OW/OB coexisted in 40% of dyads. Compared to normal weight dyads (1), each unit increase in household size and in years of maternal education decreased the risks for the coexistence of OW/OB in motherchild dyads (OR=0.72, 95% IC 0.55-0.94, P=0.015; OR=0.70, 95% IC 0.52-0.94, P=0.019, respectively). Conversely, each year increase in paternal education increased the risk for OW/OB in dyads (OR=1.47, 95% CI 1.08-1.99, P=0.015). Conclusions: Results suggest that household size and parental education contribute to shape BMI-based nutritional status in this sample of mother-child dyads. A higher level of maternal education acts as a protective factor against OW/OB in mothers and children.